Daily exercises uptake and associated factors among Social Security and National Insurance Trust pensioners in the Greater Accra Region of Ghana - Myles Ongoh; Kwamina Abekah-Carter; Edmond A-iyeh; Williams Agyemang-Duah (BMC, 2024)
Abstract Background With a growing body of evidence highlighting the positive impact of regular physical activity or exercise on achieving healthy aging, it is important to gain insight into the factors influencing daily exercises uptake. However, to the best of our knowledge, no study has been focused on factors predicting daily exercises uptake among pensioners, who form a substantial portion of Ghana's aging population. The goal of this preliminary study was to estimate the factors associated with daily exercises uptake among Social Security and National Insurance Trust (SSNIT) pensioners in Ghana. Methods Data for this study came from a cross-sectional study on survival strategies and quality of life among SSNIT pensioners in the Greater Accra Region of Ghana. Cluster and stratified sampling techniques were used to recruit the study participants. The analytic sample was 410 participants. Multivariable binary logistic regressions were used to estimate factors associated with daily exercises uptake among the participants. The significance of the test was pegged at a p-value of 0.05 or less. Results The results showed that 62% of the participants self-identified as male, 47.6% were aged between 60 and 64 years, 52.7% were employed in the public sector and 44.4% performed daily exercises. The results showed that those who were aged 60-64 years (AOR: 1.197, 95% CI: 1.019-1.405), aged 65-69 years (AOR:1.254, 95% CI: 1.071-1.468), who do not incur expenditure on their household in a month (AOR: 1.519, 95% CI: 1.127-2.046), earned less than GH¢260 (AOR: 1.221, 95% CI: 1.018-1.465), accessed/utilized herbalist medical services (AOR: 1.252, 95% CI: 1.129-1.388), very dissatisfied (AOR: 1.637, 95% CI: 1.242-2.157) and dissatisfied (AOR: 1.516, 95% CI: 1.212-1.896) with their sex life were more likely to undertake daily exercises and this was statistically significant. The results again demonstrated that participants who joined fitness club (AOR: 0.685, 95% CI: 0.614-0.764) and those who were very dissatisfied with their health services access/use (AOR: 0.598, 95% CI: 0.363-0.984) were less likely to undertake daily exercises and this was statistically significant. Conclusion Findings of this study have provided important insights for policy makers and thus constitute a useful framework to help plan and shape future policies and programs on daily exercises uptake among pensioners in Ghana and other geographical contexts with similar cultural, demographic, and socio-economic characteristics.